Comparasion of International and Indonesian Green Building Standards: Opportunities for Regulatory Harmonisation - Stephanus Wirawan Dharmatanna; Wido Hintono; Cherielyn Wijaya; Adeline Adeline; Stefanus Christian (DEARSIP : Journal of Architecture and Civil, 2026)
The building sector accounts for nearly 40% of global energy-related emissions, positioning it as a critical area for climate change mitigation and sustainable development. In line with the Paris Agreement, Indonesia has committed to reducing emissions by 29% unconditionally and up to 41% with international support by 2030. Compared to other G20 members, however, Indonesia’s Nationally Determined Contribution (NDC) remains modest, with the building sector underrepresented in its roadmap. Strengthening green building regulation is therefore essential to closing this gap. This study conducts a comparative analysis of three international rating systems—LEED (United States), Green Mark (Singapore), and Green Star (Australia)—and two Indonesian frameworks: the Greenship Rating System and Banyuwangi Regency Regulation No. 1 of 2022. Using a qualitative documentary approach, the research evaluates these frameworks across three dimensions: core criteria, assessment mechanisms, and contextual adaptation. Secondary data were drawn from official certification guidelines, regulatory documents, and published case studies, including Banyuwangi International Airport, which achieved Greenship Gold Certification under the municipal regulation. The findings indicate that while international systems emphasize comprehensiveness, innovation, and performance verification, Indonesian frameworks prioritize tropical adaptation and regulatory compliance. The Banyuwangi case demonstrates the potential of local governments to institutionalize sustainability but also highlights the limitations of narrow regulatory scope. The study identifies four strategies for harmonization: integrating LEED’s verification mechanisms, Green Mark’s tropical efficiency benchmarks, Green Star’s social dimensions, and scaling progressive local initiatives nationally. By adopting these strategies, Indonesia can enhance the global credibility of its green building frameworks, strengthen the building sector’s contribution to its NDC 2030 targets, and reduce the gap with other G20 countries, thereby advancing both national and global climate goals.